Penentuan Status Mutu Air Sungai Antokan, Kabupaten Agam, Sumatera Barat Dengan Metode Indeks Pencemaran dan Upaya Pengendaliannya - Kurniawan, Jefri; Barlian, Eri; Yuniarti, Elsa; Handayuni, Linda (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), Politeknik Negeri Cilacap, 2025)
Rivers are an important part of the ecosystem that plays a role in environmental control. Excessive utilization of rivers in economic and social aspects can reduce the function of rivers as environmental control which results in pollution that damages the environment. Pollution pressure on rivers basically requires special attention where there are 16,487 polluted rivers. The increase in human population is one of the triggers for river pollution because people will live and live and open production lands on the banks of the river. In addition, population growth also increases anthropogenic activities carried out by humans on the riverside. The Antokan River is located in Agam Regency that has a vital function to the local ecosystem. The fast population growth in Agam Regency basically also creates a threat of pollution to the Antokan River. This requires efforts to define the level of quality conditions of the Antokan river waters as a control effort. This control effort uses the pollution index method where this method is an approach used to evaluate overall water quality based on several specific water quality parameters. The findings of the study illustrate that the quality of the Antokan River at several sampling points has good quality standards and several other points are in a lightly polluted condition. Based on the established water quality status, recommendations for controlling the Antokan River using a domestic wastewater management system and water quality protection and management planning were developed. Keywords: River; Pollution Index; Quality Status; Antokan